Combination of Radiation Therapy and Immunotherapy in the Treatment of Melanoma - Sylwia, Szablewska; Magdalena, Adamczak-Sobczak (Journal of Hematology and Oncology Research, 2017)
Melanoma is considered to be a very aggressive cancer due to its rapid growth, early and multiple metastases and limited response to standard treatment. Many researchers have hypothesized that the combination of radiation therapy and immunotherapy in the treatment of melanoma primary tumors and metastases improves the efficiency of these methods as compared to their use separately. Therefore, combined therapy is an increasingly popular topic in radiation oncology. Although the mechanism of immune response to ionizing radiation remains unclear, known are the factors involved in the immune response, including NK and CD8(+) T cells. Many studies have demonstrated the importance of inflammatory factors, primarily cytokines, in the response to ionizing radiation. In turn, many cytokines released in an irradiated organ, such as tumor necrosis factor α (TNFα), interleukins IL1 and IL6 and transforming growth factor beta (TGFβ), can induce the production of significant amounts of reactive oxygen species that are associated with the induction of DNA damage in tumor cells. In relation to anticancer immunotherapy, the clinical data obtained to date can encourage future studies combining radiation therapy and the inhibitors of cell division checkpoints in the treatment of advanced melanoma. In a recent study, melanoma cell lines became more sensitive to radiation after BRAF inhibition, which provides a potential synergistic mechanism of BRAF inhibitor (BRAFi) combined with radiation therapy for better effects of treatment.  In this article, we present a systematic review of the literature on the use of the combination of radiation therapy and immunotherapy in the treatment of melanoma.
Keywords: melanoma; regulatory T cells; CD4+; CD25+; FoxP3; CTLA-4; BRAF; ipilimumab; radiation therapy.